2017
DOI: 10.14311/app.2017.13.0055
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Mechanical Performance of Concrete Used as Recycled Raw Material in Cementitious Composite

Abstract: Abstract. The reduction of industrial pollution is recently one of main goals over all fields. In civil engineering, re-cycling of structural waste provides wide opportunity contributing this effort. This paper focus on re-use of concrete waste, which after further processing can be used in new constructions as partial supplement to the mixture. To investigate the impact of re-cycled concrete addition, it is necessary to determine mechanical and structural parameters of individual phases in the "raw" material.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…SEM was used to study the mechanical behaviour and microstructure features of interfacial transition zones in AC mixtures containing recycled concrete aggregate. Results showed that SEM images revealed the presence of various types of mineral phases and voids, which contributed to the mechanical behaviour and durability of the AC mixtures [37].…”
Section: Ac Microstructure Analysis Using Semmentioning
confidence: 99%
“…SEM was used to study the mechanical behaviour and microstructure features of interfacial transition zones in AC mixtures containing recycled concrete aggregate. Results showed that SEM images revealed the presence of various types of mineral phases and voids, which contributed to the mechanical behaviour and durability of the AC mixtures [37].…”
Section: Ac Microstructure Analysis Using Semmentioning
confidence: 99%